Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.36712/sdi.v28i3.24994
|View full text |Cite
|
Sign up to set email alerts
|

Pesantren during the Pandemic: Resilience and Vulnerability

Abstract: This paper describes PPIM’s research entitled “ The Impact and Resilience of Senior High School Education Institutions in Islamic Boarding Schools (Pesantren) during the COVID-19 Pandemic Crisis: Study of 15 Pesantren in Jakarta, Banten, and West Java” (PPIM, 2021). This study is to observe the resilience and vulnerability of a pesantren towards the spread of the COVID-19 pandemic. In addition, the research also aims to explore the role of nyai (a wife of kiai, a pesantren leader) during the pandemic. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, people should continue to update their know ledge to act appropriately in preventing the COVID-19 transmission. 33,34 Furthermore, the existence of the infodemic (the rapid spread of information-both accurate and inaccurate-in the age of the internet and social media) phenomenon emphasizes the need for this effort. 35 Specifically, this study found that self-efficacy positively influenced actual use and user's satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, people should continue to update their know ledge to act appropriately in preventing the COVID-19 transmission. 33,34 Furthermore, the existence of the infodemic (the rapid spread of information-both accurate and inaccurate-in the age of the internet and social media) phenomenon emphasizes the need for this effort. 35 Specifically, this study found that self-efficacy positively influenced actual use and user's satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Related to the development of the instrument, questions for perceived severity and perceived seriousness were adopted from previous research (Hendarmin et al, 2021). Later, questions for reasons for using or not using the app, features of the app, perceived benefits, and perceived barriers were developed based on the previous literature (Indonesia Baik, 2023;Kondylakis et al, 2020;Nurmansyah et al, 2022).…”
Section: Instrumentmentioning
confidence: 99%